Digital Leadership, IT Strategic Alignment, and Organizational Agility: The Mediating Role of Digital Transformation Adoption in Driving Sustainable Business Performance - Tahir, Muhammad Ridwan; Irvan Prama Wijayanto; Sutrisno, Tri; Mariani, Minsani (Universitas Muhammadiyah Pontianak, 2026)
This study examines how organizational capabilities drive sustainable business performance through digital transformation adoption. Using a quantitative approach with PLS-SEM on 327 respondents, it analyzes digital leadership, IT strategic alignment, and organizational agility. Results show all capabilities positively influence digital transformation adoption, with digital leadership as the strongest predictor. Digital transformation significantly enhances sustainable business performance and partially mediates the relationship between capabilities and performance. The findings underscore that successful digital transformation depends not only on technological investment but also on the effective implementation and integration of digital practices within organizational processes. Keywords: Digital Leadership; IT Strategic Alignment; Organizational Agility; Digital Transformation; Sustainable Business Performance